Analisis Postur Kerja Dan Keluhan Muskuloskeletal Pada Petani Pemetik Cengkih Di Kabupaten Minahasa Selatan - Pandey, Blandina E.; Doda, Diana V.D.; Malonda, Nancy S. (eBiomedik, 2020)
Abstract: Musculoskeletal complaints are one of the most common health problems experienced by workers. Work-related Musculoskeletal disorders may reduce workforce productivity. This disease is caused by inconsistency between tools, humans, and work processes so often the workers do activities with awkward work posture. This study aimed to analyze the working posture and the musculoskeletal complaint of the cloves farmers in one of the villages in the district of South Minahasa. The study used analytical surveys with cross-sectional study design and the number of population taken was all members of the farmer group of 60 people. The instruments in this study are the Nordic Body Map questionnaire and the Ovako Working Posture Analysis System Assessment sheet. A statistical rank Spearman test was used to analyze the relationship between the working posture and the musculoskeletal complaint of the cloves farmers. The characteristics of the participants were mostly male within the age group of 31-50 years old. The majority of the participants have a moderate musculoskeletal complaint (68.3%). The highest complaint that the respondent felt was at the foot of (98.3%) and on the wrist (96.7%). The bivariate result shows that there were relationships between work posture and musculoskeletal complaint (p= 0.000, p = < 0.05) with the relationship level indicating moderate correlation (r = 0,590) and the direction of positive relationship. Based on the results of the research on the risk of the most working posture is at high risk (50%). This research concludes that working posture an important factor for the development of musculoskeletal complaints among Cloves farmers.Keywords: farmer, musculoskeletal, work-posture.  Abstrak: Keluhan muskuloskeletal merupakan salah satu masalah kesehatan yang paling umum ditemui pada pekerja informal. Gangguan muskuloskeletal bisa berdampak berkurangnya produktivitas tenaga kerja.  Penyakit ini disebabkan oleh karena ketidaksesuaian antara alat, manusia, dan proses kerja kerja sehingga sering kali para pekerja melakukan aktivitas dengan  postur kerja janggal. Tujuan dalam penelitian ini adalah untuk menganalisis postur kerja dan keluhan muskuloskeletal pada petani pemetik cengkih di Desa Tambelang Kabupaten Minahasa  Selatan. Penelitian ini menggunakan survei analitik dengan desain study cross sectional dan jumlah populasi yang diambil adalah seluruh anggota kelompok tani yang berjumlah 60 orang. Instrumen dalam penelitian ini adalah kuesioner Nordic Body Map dan lembar penilaian Ovako Working Posture Analysis System. Analisis yang digunakan yaitu uji statistik rank spearman. Sebagian besar petani cengkeh melaporkan mengalami keluhan Muskuloskeletal yang sedang (68,3%). Keluhan tertinggi yang dirasakan responden ada pada bagian kaki yaitu 98,3% dan keluhan kedua tertinggi ada pada bagian pergelangan tangan yaitu 96,7%. Hasil analisis bivariate menemukan bahwa terdapat hubungan antara postur kerja dan keluhan muskuloskeletal (p= 0,000, p=<0,05) dengan tingkat hubungan menunjukkan korelasi sedang (r=0,590) dan arah hubungan positif. Berdasarkan hasil penelitian risiko postur kerja terbanyak ada pada  risiko tinggi yaitu 50%. Kesimpulan dari penelitian ini yaitu postur kerja merupakan faktor yang penting  yang dapat menyebabkan keluhan muskuloskeletal pada petani pemetik cengkih.Kata Kunci: petani, muskuloskeletal, postur kerja.